PENGARUH KOMUNIKASI TERHADAP KINERJA KARYAWAN PT TRISULA TEXTILE INDUSTRIES - Elly Watti Noorhan; Nihayatul Adawiyah; Sanifah Novitasari Lingga (SECAD, 2025)
The main problem that will be studied in this research is employee performance at PT Trisula Textile Industries, which is thought to be influenced by communication factors. how big is the influence of communication on the performance of PT Trisula Textile Industries employees. The author's aim in conducting this research is to determine and analyze the communication and performance of PT Trisula Textile Industries employees, as well as the influence of the independent variable on the dependent variable. The method used in this research is a quantitative descriptive approach. The respondents in this research were 30 employees of PT Trisula Textile Industries. The data in this research is primary data, where the data is obtained from respondents' answers to the questionnaire that the author distributed. The results of the data analysis that the author has carried out show that there is a significant influence of communication, both simultaneously and partially, on the performance of PT Trisula Textile Industries employees.